2020
DOI: 10.21203/rs.3.rs-54691/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations of blood essential and toxic metal(loid)s with both disease severity and mortality in patients with COVID-19: a retrospective study

Abstract: Background The variations and dynamics of blood essential and toxic metal(loid)s in patients with COVID-19 still remains unclear.Methods A retrospective study was performed in a cohort of confirmed COVID-19 patients for their whole blood levels of essential and/or toxic metal(loid)s including magnesium, calcium, chromium, manganese, iron, copper, zinc, arsenic, cadmium, mercury, thallium and lead according to the disease severity and outcome.Results Compared to the non-severe COVID-19 patients, Whole blood cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
8
2
Order By: Relevance
“… Calder, 2020 Calder et al, 2020 Celik et al, 2021 Chaturvedi et al, 2004 Culbertson and Culotta, 2021 de Almeida Brasiel, 2020 de Jesus and de Araú jo Andrade, 2020 Ersö z and Y ı lmaz, 2021 Grzywa-Celiń ska et al, 2020 Hultman and Pollard, 2015 Moghaddam et al, 2020 Muhammad et al, 2021 Rahman and Idid, 2021 Skalny et al, 2020 Vogel-Gonzá lez et al, 2021 Zeng et al, 2021 .…”
Section: Uncited Referencementioning
confidence: 99%
“… Calder, 2020 Calder et al, 2020 Celik et al, 2021 Chaturvedi et al, 2004 Culbertson and Culotta, 2021 de Almeida Brasiel, 2020 de Jesus and de Araú jo Andrade, 2020 Ersö z and Y ı lmaz, 2021 Grzywa-Celiń ska et al, 2020 Hultman and Pollard, 2015 Moghaddam et al, 2020 Muhammad et al, 2021 Rahman and Idid, 2021 Skalny et al, 2020 Vogel-Gonzá lez et al, 2021 Zeng et al, 2021 .…”
Section: Uncited Referencementioning
confidence: 99%
“…This study identified a link between chronic kidney disease and death. In another study [22], the concentration of magnesium was measured in whole blood samples showing a significantly lower magnesium level in severe than in nonsevere Covid-19 patients. Lastly, in a small cohort study [23], hypermagnesemia prevalence was significantly higher in the ICU group than in the outpatient group.…”
Section: Univariate Analysismentioning
confidence: 99%
“…and the elderly. However, data about the magnesium status during the Covid-19 are scarce [20][21][22][23].…”
mentioning
confidence: 99%
“…Available information suggests that zinc deficiency is associated with increased disease severity of the COVID-19 [5] . In a comprehensive metal(loid)s analysis, compared to the non‐severe COVID‐19 patients, the whole blood chromium, calcium, and copper levels were higher, while the levels of zinc, magnesium, manganese, iron, lead, arsenic, and thallium were lower in the severe patients with COVID-19 [6] . Depending on age and gender, the recommended daily allowance for zinc varies between 2 to 13 mg/day, with the tolerable upper intake level for zinc is set at 40 mg/day by the Institute of Medicine (IOM).…”
Section: Zinc: An Essential Trace Elementmentioning
confidence: 97%